Hydroxylation of benzene by hydrogen peroxide over titanium silicalite-1 catalyst in a periodically operated three phase, co-current downflow packed bed reactor - Pimporn Chaicharus (Chulalongkorn University, 2012)
Thesis (M.Eng.)--Chulalongkorn University, 2003